Cancer stem cell plasticity in glioblastoma multiforme: a perspective on future directions in oncolytic virotherapy - Kim, DS (Future Medicine Ltd, 2020)
The cancer stem cell (CSC) hypothesis suggests that a rare population of stem-like cells underpin tumorigenesis. Oncolytic viruses (OVs) demonstrate novel mechanisms of targeting the elusive CSCs with greater selectivity – promising therapeutic potential against solid tumors such as glioblastoma (GBM) that are resistant to conventional treatment. In general, OVs have failed to translate the efficacy from bench to bedside. The success of OVs rely on the hypothesis that eliminating CSCs is key to preventing recurrence. However, newly emerging evidence of CSC plasticity challenge this hypothesis by proposing that the CSC pool can be regenerated from non-CSCs post-treatment. We review this evidence surrounding the CSC hypothesis to propose an original perspective on why several advanced OVs may be failing to reflect their true potential in clinical trials. We argue that preventing non-CSC to CSC dedifferentiation may be critical to achieving long-term treatment efficacy in future OV clinical trials.